Faktor Risiko Obesitas dan Profil Lipid Darah pada Mahasiswa Baru Universitas Riau - Elda Nazriati; Arfianti Arfianti; Ismawati Ismawati (Fakultas Kedokteran Universitas Riau, 2010)
Obesity is a substansial public-health crisis in numerous developing country including Indonesia. Morbidity and mortalityin adult population is increased in individuals who were overweight in adolescence even if they lose the extra weightduring adulthood. Many factor influencing occurence of obesity, such as food pattern and activity pattern.The aims ofthis study was to describe risk factor of obesity of obese students. Samples were 2006’s obese students of RiauUniversity who had doing medical Check-up in Balai Kesehatan of Riau University. A descriptive study conducted on27 obese students in Riau University class 2006. variables of this study are risk factor of individual and family, foodpattern, and activity pattern. Obese criterian was taken by measured BMI. Food pattern and activity pattern was takenby using questionnaire. This study showed that 15 students (55,5 %) wereobese II (BMI > 30), 100 % students arecentral obesity, 59% students had mild consumtion risk factor and 22% students had high consumtion risk factor. 16% student had mild and 74 % student had high activity risk factor.